2002
DOI: 10.1002/1521-4095(20020116)14:2<144::aid-adma144>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymer Composites with High Optical Gain Based on Pseudo-Photorefraction

Abstract: Asymmetric two‐beam coupling without a space‐charge field or electro‐optical and orientational effects was detected in hemicyanine‐dye‐containing polymer composites. This phenomenon, termed “pseudo‐photorefraction” by the authors, appears to arise from movement of the interference pattern and mass transport within the polymer matrix. Large optical gain effects and amplification up to 30 % qualify the materials for simple yet highly effective photorefractive devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Recently, it has been reported that the asymmetric two beam coupling was occurred in the unpoled centrosymmetric azo-dye doped silica-gel composites with photosensitizer and photoconductor of carbazole derivative type [5], polymer composites containing hemicyanine dye [6] and monolithic molecular glass with electron acceptor and donor moieties in the molecule [7] without applying external electric field. We reported that PVCz/NPP/Plasticizer/ TNF system gave large optical gain of 224 cm À1 due to asymmetric beam coupling, and high diffraction of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the asymmetric two beam coupling was occurred in the unpoled centrosymmetric azo-dye doped silica-gel composites with photosensitizer and photoconductor of carbazole derivative type [5], polymer composites containing hemicyanine dye [6] and monolithic molecular glass with electron acceptor and donor moieties in the molecule [7] without applying external electric field. We reported that PVCz/NPP/Plasticizer/ TNF system gave large optical gain of 224 cm À1 due to asymmetric beam coupling, and high diffraction of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, optical gain due to asymmetric energy transfer usually occurs in non‐centrosymmetric media in the presence of an external electric field. However, there have been several reports of asymmetric two‐beam coupling in the absence of an applied external electric field for carbazole‐based PR polymers, azobenzene derivatives in matrices and carbazole–azobenzene monolithic compound‐based PR polymers . Asymmetric two‐beam coupling has also been reported in high‐ T g non‐poled PR polymers with carbazole and azobenzene moieties as pendant groups .…”
Section: Two‐beam Coupling In a Centrosymmetric Environmentmentioning
confidence: 99%
“…Thus, usual asymmetric energy transfer occurs in the presence of an external electric field. However, several reports on asymmetric two-beam-coupling gains without the application of an external electric field have been reported for carbazole-based PR polymers, 93,94,111,112 azobenzene derivatives in matrices 113 and carbazole-azobenzene monolithic compound-based PR polymers. [114][115][116] Asymmetric two-beam coupling has also been reported in high T g non-poled PR polymers with carbazole and azobenzene moieties as pendant groups.…”
Section: Pr Response In a Centrosymmetric Environmentmentioning
confidence: 99%